Molecular Cloning, Expression and Transport Activity of SaNPF6.3/SaNRT1.1, a Novel Protein of the Low-Affinity Nitrate Transporter Family from the Euhalophyte Suaeda altissima (L.) Pall. - Olga I. Nedelyaeva; Dmitrii E. Khramov; Lyudmila A. Khalilova; Alena O. Konoshenkova; Anastasia V. Ryabova; Larissa G. Popova; Vadim S. Volkov; Yurii V. Balnokin (Membranes, 2023)
The SaNPF6.3 gene, a putative ortholog of the dual-affinity nitrate (NO3−) transporter gene AtNPF6.3/AtNRT1.1 from Arabidopsis thaliana, was cloned from the euhalophyte Suaeda altissima. The nitrate transporting activity of SaNPF6.3 was studied by heterologous expression of the gene in the yeast Hansenula (Ogataea) polymorpha mutant strain Δynt1 lacking the original nitrate transporter. Expression of SaNPF6.3 in Δynt1 cells rescued their ability to grow on the selective medium in the presence of nitrate and absorb nitrate from this medium. Confocal laser microscopy of the yeast cells expressing the fused protein GFP-SaNPF6.3 revealed GFP (green fluorescent protein) fluorescence localized predominantly in the cytoplasm and/or vacuoles. Apparently, in the heterologous expression system used, only a relatively small fraction of the GFP-SaNPF6.3 reached the plasma membrane of yeast cells. In S. altissima plants grown in media with either low (0.5 mM) or high (15 mM) NO3−; concentrations, SaNPF6.3 was expressed at various ontogenetic stages in different organs, with the highest expression levels in roots, pointing to an important role of SaNPF6.3 in nitrate uptake. SaNPF6.3 expression was induced in roots of nitrate-deprived plants in response to raising the nitrate concentration in the medium and was suppressed when the plants were transferred from sufficient nitrate to the lower concentration. When NaCl concentration in the nutrient solution was elevated, the SaNPF6.3 transcript abundance in the roots increased at the low nitrate concentration and decreased at the high one. We also determined nitrate and chloride concentrations in the xylem sap excreted by detached S. altissima roots as a function of their concentrations in the root medium. Based on a linear increase in Cl− concentrations in the xylem exudate as the external Cl− concentration increased and the results of SaNPF6.3 expression experiments, we hypothesize that SaNPF6.3 is involved in chloride transport along with nitrate transport in S. altissima plants.